2014
DOI: 10.1002/nme.4803
|View full text |Cite
|
Sign up to set email alerts
|

An extended Layerwise method for composite laminated beams with multiple delaminations and matrix cracks

Abstract: For the delamination and matrix crack prediction of composite laminated structures, the methods based on the damage mechanics and fracture mechanics are most commonly used. However, there are very few methods that can accurately simulate the delaminations together with matrix cracks, although the in-plane matrix cracks always exist alongside the delaminations under impact loading. In this work, an extended layerwise method is developed to model the composite laminated beam with multiple delaminations and matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…Extended layerwise method was used for composite laminated beams, plates, and shells by some researchers. Li et al (2015) presented an extended layerwise method to simulate the multiple delaminations together with in-plane matrix cracks for laminated composite beams. The results demonstrated that the presented method was well suited to the static problem of the laminated composite structures with complex damage form.…”
Section: Layerwise Theorymentioning
confidence: 99%
“…Extended layerwise method was used for composite laminated beams, plates, and shells by some researchers. Li et al (2015) presented an extended layerwise method to simulate the multiple delaminations together with in-plane matrix cracks for laminated composite beams. The results demonstrated that the presented method was well suited to the static problem of the laminated composite structures with complex damage form.…”
Section: Layerwise Theorymentioning
confidence: 99%
“…Li et al. 14 investigated the influences of the delamination size and location on the maximum displacements of the composite laminated beam, considering the matrix crack simultaneously. Further investigations on the buckling of composite plates containing a delamination of an arbitrary shape have been also reported in the literature by Ovesy et al.…”
Section: Introductionmentioning
confidence: 99%
“…Fracture mechanics methods have been the major tool used for modeling the mechanical behavior of interface cracks in bimaterial media. Generally speaking, these methods can be grouped into 2 families: linear elastic fracture mechanics (LEFM) approaches [1][2][3][4][5][6][7][8][9] and cohesive zone models. [10][11][12][13][14][15][16][17][18][19][20][21][22] Recently, Yuan and Fish 23 developed a continuum damage mechanics-based dual-purpose model to simultaneously describe delamination as well as ply failure.…”
Section: Introductionmentioning
confidence: 99%